A new species of the genus Dzhugesia Wehrli (Lepidoptera: Geometridae, Ennominae) from Iran - Kamyab, Fariba; Makhov, Ilya A.; Mokhtari, Azizollah (Zootaxa, 2025)
A series of geometrid moths belonging to the little-known genus Dzhugesia Wehrli, 1936, were collected in southern Iran (Kerman Province). Both morphological characters and DNA barcoding confirm that the specimens represent a new species, herein described as D. alierfani Makhov & Kamyab sp. nov. Additional remarks on the diagnostic characters of the genus Dzhugesia are provided. The relationships between Dzhugesia and the closely related genera Crocallis and Scodiomima are also discussed. Furthermore, the misidentification of a specimen previously submitted to the BOLD database is corrected. This study constitutes the first record of the genus Dzhugesia from Iran. D. miatleuskii is recorded as new species for the fauna of Iran.